Variations in complete blood count parameters during pregnancy and their association with maternal age and gravidity - Mohieldin Abass Elsayid; Maha B Alqahtani; Seham A Khashwayn; Rouzana F Khayat; Farah A Alsibyani; Sara F Almalki; Areej Y Alyahyawi; Naif S Sannan; Amir Abushouk (Wolters Kluwer Medknow Publications, 2024)
Introduction: Complete blood count (CBC) parameters change throughout pregnancy and are thought to be one of the factors affecting the pregnancy's outcome. This study aims to report variations in CBC parameters throughout pregnancy and their association with maternal age and gravidity. Methods: This is a retrospective cohort study in which CBC data from 234 pregnancies with normal full-term delivery in 2020 were evaluated and grouped depending on maternal age and gravidity. Results: Hemoglobin levels decreased significantly from the first to the second trimester (P < 0.0001) and then slightly increased in the third trimester. Red blood cells decreased significantly from the first to the second trimester and remained unchanged in the third trimester (P < 0.0001). Packed cell volume decreased significantly from the first to the second trimester (P < 0.0001) and then increased in the third trimester (P = 0.0178). White blood cells (WBCs) increased significantly from the first to the second trimester (P < 0.0001) and then remained stable in the third trimester. Neutrophils and lymphocytes showed opposed tendencies, with neutrophils increasing significantly from the first to the second trimester (P < 0.0001) and then remaining stable in the third trimester (P = 0.42). Lymphocytes decreased significantly from the first to the second trimester (P < 0.0001) and continued to decrease in the third trimester (P < 0.0001). Monocytes increased significantly from the first to the third trimester (P = 0.0051). Platelets decreased significantly from the first to the third trimester (P < 0.0001). Gravidity showed a negative correlation with WBC count (r = −0.17, P = 0.01) and a positive correlation with eosinophil levels (r = 0.14, P = 0.0376). Spearman's correlations revealed no significant differences in maternal age groups. Conclusions: Our findings provide useful insight for physicians and policymakers in assessing CBC during pregnancy and providing optimal care. Furthermore, the associations between gravidity and WBC (negative) and eosinophil levels (positive) point to a potential effect of reproductive history on immune function, necessitating additional research in this area.